2009
DOI: 10.1007/s12010-009-8696-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain Length of Alcohol on the Lipase-Catalyzed Esterification of Propionic Acid in Supercritical Carbon Dioxide

Abstract: The esterification of propionic acid was investigated using three different alcohols, namely, isopropyl alcohol, isobutyl alcohol, and isoamyl alcohol. The variation of conversion with time for the synthesis of isoamyl propionate was investigated in the presence of five enzymes. Novozym 435 showed the highest activity, and this was used as the enzyme for investigating the various parameters that influence the esterification reaction. The Ping-Pong Bi-Bi model with inhibition by both acid and alcohol was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 41 publications
0
12
0
5
Order By: Relevance
“…It is suggested that the use of microwaves as a heat source to change the interactions between the enzyme and its microenvironment prevent the thermal denaturation of the enzyme. Also, the support provides stability to the enzyme so that it does not degrade at high temperatures [19]. The effect of microwave radiation on enzyme activity is a function of enzyme hydration [20].…”
Section: Effect Of Temperature On Esterification Under Microwave Irramentioning
confidence: 99%
“…It is suggested that the use of microwaves as a heat source to change the interactions between the enzyme and its microenvironment prevent the thermal denaturation of the enzyme. Also, the support provides stability to the enzyme so that it does not degrade at high temperatures [19]. The effect of microwave radiation on enzyme activity is a function of enzyme hydration [20].…”
Section: Effect Of Temperature On Esterification Under Microwave Irramentioning
confidence: 99%
“…In spite of the decreased residual activity of the immobilized lipase after the treatment with supercritical CO 2 , the enzyme can still catalyze reactions in supercritical media efficiently, as demonstrated by several studies [40,[51][52][53][54][55]. Therefore, the study of the esterification reaction of oleic acid ( Figure 4) using immobilized Lipozyme 435 as a catalyst was carried out in supercritical CO 2 .…”
Section: Effect Of Supercritical Co 2 On the Esterefication Reactionmentioning
confidence: 99%
“…As a green medium, supercritical carbon dioxide (scCO2) is one of most suitable solvents for lipase catalysis used to produce flavors esters in the food industry. The lipase-biocatalyzed (Novozym 435) esterification of propionic acid with isopropyl alcohol, isobutyl alcohol and isoamyl alcohol in supercritical carbon dioxide 48 has been reported. The initial reaction rate decreases when the chain length of the primary alcohol increases.…”
Section: Asian Journal Of Chemistry Asian Journal Of Chemistrymentioning
confidence: 99%